2008
DOI: 10.1007/s12272-001-1243-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calcium channel blockers on hyaluronidase-induced capillary vascular permeability

Abstract: Inflammation and increased capillary permeability is a significant aspect of the pathogenesis of many diseases including atherosclerosis. L-type calcium channel blockers (CCB) are commonly used as cardiovascular drugs. Amlodipine, lacidipine, and nicardipine were evaluated for anti-inflammatory activity on the paw oedema produced by carrageenan. The effect of these drugs was compared with the activity of indomethacin. Their effects on vascular permeability were also tested by hyaluronidase-induced capillary pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Halici et al. reported that nicardipine can be efficient anti‐inflammatories, and can also significantly decrease capillary permeability in the rats study [31]. Gomes et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Halici et al. reported that nicardipine can be efficient anti‐inflammatories, and can also significantly decrease capillary permeability in the rats study [31]. Gomes et al.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there are no reports of nicardipine for the treatment of PD. Halici et al reported that nicardipine can be efficient anti-inflammatories, and can also significantly decrease capillary permeability in the rats study [31]. Gomes et al reported that nicardipine improves experimental asthma by impairing inflammation, and could potentially be beneficial in the treatment of asthma [32].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we demonstrated that amlodipine exerts anti-inflammatory, anti-osteoporotic, and protective effects against ovarian ischemia-reperfusion (I/R) damage [12,13]. Amlodipine has also been clinically and experimentally shown to have antiatherogenic effects because it decreases and/or blocks inflammation from forming in the atheroma plaques on the vascular endothelium by inhibiting nitric oxide synthase activity [14].…”
Section: Introductionmentioning
confidence: 99%
“…Investigations that have tried to modify the charge of the GC (15,54) or to reduce the impact of it via enzymatic ESL degradation have demonstrated increases in the glomerular permeability to albumin as a consequence of such pertubations (27,28,51). For example, hyaluronidase (hyase), which cleaves hyaluronan, chondroitin, and chondroitin sulfate, has been demonstrated to decrease the ESL and increase the permeability of peripheral and glomerular capillaries (16,21,25,27,28,36). In some of these studies, negatively charged albumin [radius 36 Å and sieving coefficient () ϳ 0.0001 (22)], which according to pore theory (the two-pore model) would permeate the GFB exclusively through larges pores (radius ϳ115-120 Å), has been compared with hyperpermeable neutral Ficoll (radius 36 Å) passing mainly through small pores (radius ϳ37.5 Å) and having a high (ϳ0.1) (2).…”
mentioning
confidence: 99%